TUNGOLINANGAN heritage-generative architecture on the Las Piñas LRT-1 Station - Amper, Tristan Raine Anthoni M.
Las Piñas city’s urban identity is associated with its purpose as an urban gateway between NCR and CALABARZON; and its historical corridor rich in Hispanic Heritage. This urban fabric — transport and culture identities — experience the negative effects of urbanization. The corridor has low accessibility due to its isolated location and congestion. Las Piñas’s main thoroughfares have long been riddled by traffic and congestion due to impervious sprawls and vehicular privatization. These contribute to poor public commute experience and cultural inaccessibility. The extension of the LRT Line-1 and addition of the Las Piñas station present an opportunity for an architecture that aims to coalesce these urban facets. Like many other cities in Metro Manila, there is little research and development on the intersection of both urban sectors. The project takes advantage of inherent opportunities to present an architectural design geared towards Sustainable Mobility and Cultural Accessibility — aiding in the alleviation of public transport congestion; improving commuter environments; and enriching Las Piñas’ cultural heritage identity amongst its residents. The project explores Architectural Heritage Interpretation, Concept Layout Model of Terminals, Transport Intermodality and Park-and-Ride Facility theories. The identified site – the Las Pinas LRT-1 Station – is proposed with a public transportation terminal meshed with cultural spaces, forming both a transport node and a place of cultural congregation and exploration. The proposed design of the LRT station can present a new perspective as to how our railway and transit in Metro Manila can become transcendent urban spaces.